Born in another country: women's experience of labour and birth in Queensland, Australia. - Hennegan, J; Redshaw, M; Miller, Y (2014)
BACKGROUND: Women born outside Australia make up more than a fifth of the Queensland birthing population and like migrants in other parts of the world face the challenges of cultural dislocation and possible language barriers. Recognising that labour and birth are major life events the aim was to investigate the experiences of these women in comparison to native-born English speaking women. METHODS: Secondary analysis of data from a population based survey of women who had recently birthed in Queensland. Self-reported clinical outcomes and quality of interpersonal care of 481 women born outside Australia who spoke a language other than English at home were compared with those of 5569 Australian born women speaking only English. RESULTS: After adjustment for demographic factors and type of birthing facility, women born in another country were less likely to be induced, but more likely to have constant electronic fetal monitoring (EFM), to give birth lying on their back or side, and to have an episiotomy. Most women felt that they were treated as an individual and with kindness and respect. However, women born outside Australia were less likely to report being looked after 'very well' during labour and birth and to be more critical of some aspects of care. CONCLUSION: In comparing the labour and birth experiences of women born outside the country who spoke another language with native-born English speaking women, the present study presents a largely positive picture. However, there were some marked differences in both clinical and interpersonal aspects of care.